COMBINING METHOD FOR ESTIMATING SUSCEPTIBILITY OF LOW QUANTITY SAMPLES AND ANALYSIS OF FREQUENCY-DEPENDENT SUSCEPTIBILITY - FITRIANI (NIM : 30207003); Tim Pembimbing : Prof. Satria Bijaksana, Ph.D; Prof. Dr.rer.nat. Um, DINI
Magnetic susceptibility measured in low magnetic field is a common parameter used in rock magnetic method. Instrument that used to measure magnetic susceptibility is known as magnetic susceptibility meters. Recently, magnetic susceptibility studies have been developed in line with the development in instrumentation and measuring techniques. However, on the other hand there is problem associated with the sample standard size specifications to be used. In general, 10 cm3 is used as measurement of standard-sized samples. Measurement with sample volume less than the standard size can lead to the deviation (error) that affects the analysis. Other problem that might be arising is related with measurement range in which the susceptibility meter has a maximum measured value. Measurement of the strongly magnetic sample in which the magnetic susceptibility value exceeds the maximum value could also cause deviations in the measurement results. The most common method of measuring substances that are either too low in quantity or magnetically too strong is placing a small amount of substance (< 10 cm3 in volume) in standard-size holder and positioning it preferably in the center of sensor. The capability of susceptibility meter to respond well to samples with low volume should be studied further. Related to this, in this research, the accuracy of measurement used Bartington MS2 magnetic susceptibility meter with a type B sensor (Bartington MS2B), as a susceptibility meter is widely used in the study of methods of rock magnetism, was tested against sample volume. The test was conducted by designing a set of internal sample holder with varied diameters from 3 – 18 mm as the additional holder that can be placed in the standard sample holder. The tests were carried out on YO-8087, R-9998 and MO-4232. The mass of materials used range from 0.0776 - 2.8290 gram, 0.1610 - 5.6901 gram and 0.0706 - 3.0250 gram, for YO-8087, R-9998 and MO-4232, respectively. The measurement results show that the use of samples which less than the standard size, although the sample was placed in the center of the sensor, still produces a significant deviation. Deviation using of the smallest internal holder (3 mm) and the largest internal holder (18 mm) are 14.2% and 0.9%, respectively for YO-8087 and 6.8% and 0.6%, respectively for R-9998. Meanwhile, the deviation for MO- 4232 could not be determined due to its volume susceptibility exceeds 9999 × 10-5 SI. The test results provide motivation to propose another method by combining tested substances with other substances as reference whose magnetic susceptibility are known (combining method). The combining method was tested in variety of substances ranging from industrial samples to particulates of vehicle exhaust. Measurement of combinations between tested and reference substances in various proportions lead to an estimation of mass-specific magnetic susceptibility of tested substance through graphical analyses. Combining method provides estimation of magnetic susceptibility with a deviation of about 1% for two industrial magnetic substances (YO-8087 and R-3098) and about 3% for lateritic soil and vehicle-derived particulate. In this research, magnetic susceptibility as function of frequency (frequencydependent susceptibility, FDS) was also studied. In general, FDS parameters obtained through measurements using a Bartington MS2B which has two operating frequencies. To analyze FDS in more detail, it is necessary to use a wide range of operating frequencies. For this reason, other than MS2B Bartington, in this study another instrument with a wide operating frequency designed by Kodama (2010) was also used. In addition to above two instruments which are frequency domain instruments, a time domain instrument, namely magnetic viscosity meter (MVM1), was also used. Measurements using both types of instruments are tested in industrial magnetic substances and lateritic soil. The results infer that the magnetic susceptibility of industrial magnetic substances showed no dependence on frequency (frequency-independent susceptibility). In contrast, measurements on lateritic soil showed a frequency dependence of the magnetic susceptibility. The MVM1 measurement results show that the slope of the curve based on log-log indicated no significant difference between the lateritic soils which have significant FDS with industrial magnetic substance which show frequency-independent susceptibility.